A Case Study on Marital Satisfaction of a Married Couple Living in The Same House with Their Parents - Ayu, Selly Candra; Hakim, Lukman (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Marital satisfaction is a pleasant feeling in living a happy life with a partner, interactive communication, freedom in the household. Couples who live in the same house with their parents experience a lot of emotional stress, lack of quality with their spouse, dominating childcare is the parents, couples do not have the freedom to do activities and solve problems and the problem-solving process involves parents. The objectives of this study are (1) To explore marital satisfaction in couples who live in the same house with parents, (2) Implementation of satisfaction management in marriage. Qualitative research method with a case study approach. Data collection techniques consist of observation, interviews, and documentation. Data analysis with three stages; the first stage is data reduction, data presentation, and triangulation. The results showed: (1) Marriage satisfaction in the household is based on 5 aspects, namely: a. Age of marriage; having readiness in terms of age is able to foster a sense of responsibility and cooperation between the appropriate spouses, b. educational background and equal income, c. Educational background and equal income, and d. Educational background and equal income. Educational background and income are equal, and have a steady income, c. Religion; strength and similarity in religious activities, d. Emotional Support; understanding the conditions between spouses. Emotional support; understanding the conditions between spouses, having two-way communication, e. Differences in expectations; differences in opinion between spouses, parents and in-laws, childcare, problem solving, freedom in households. (2) Management of the application of marital satisfaction in the household, starting with the stages of situation analysis (understanding the needs in married life and readiness in the household, starting from childcare, economy, mental and problem solving), perception equalization (understanding the conditions that occur and having the same perception and goals in building a household), organizing and implementing in the household (two-way communication between spouses, solving problems together, being involved in household activities).